A Graphical Method of Adjusting a Doubly-Braced Quadrilateral of Measured Lengths when their Weights are also taken into Consideration - Bhattacharji, J. C. (The International Hydrographic Review, 2015)
An attempt has been made to develop a graphical method of precisely adjusting a doubly-braced quadrilateral of measured lengths by fitting the least squares method to different systems of weighting, without recourse to elaborate computations and trigonometrical tables. The suggested method is more simple and less time-consuming than the usual methods.